2020
DOI: 10.3892/etm.2020.9199
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic saline improves brain edema resulting from traumatic brain injury by suppressing the NF‑κB/IL‑1β signaling pathway and AQP4

Abstract: Although hypertonic saline (HS) has been extensively applied to treat brain edema in the clinic, the precise mechanism underlying its function remains poorly understood. Therefore, the aim of the present study was to investigate the therapeutic mechanism of HS in brain edema in terms of aquaporins and inflammatory factors. In the present study, traumatic brain injury (TBI) was established in male adult Sprague-Dawley rats, which were continuously administered 10% HS by intravenous injection for 2 days. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…These findings are parallel to our observations in the Rs1 -KO mouse natural history and underscore the connection between the electrical function of the eye and the fluid homeostasis of the retina. Systemic infusions of hyperosmolar fluid have been shown to reduce edema in other organs, like the brain, in the setting of acute cerebral injury (25). With this precedent, strategies leveraging fluid exchange to promote the resolution of cysts in edematous retinal conditions merit further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are parallel to our observations in the Rs1 -KO mouse natural history and underscore the connection between the electrical function of the eye and the fluid homeostasis of the retina. Systemic infusions of hyperosmolar fluid have been shown to reduce edema in other organs, like the brain, in the setting of acute cerebral injury (25). With this precedent, strategies leveraging fluid exchange to promote the resolution of cysts in edematous retinal conditions merit further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Intraventricular injection of lipopolysaccharide (LPS) also induces overexpression of AQP4 [37]. Studies have found that both NF-kappa B signaling pathway and AQP4 are involved in the regulation of cerebral edema after TBI [38]. As a calmodulin blocker, TFP has regulatory relationship with NF-kappa B signaling pathway [39].…”
Section: Discussionmentioning
confidence: 99%
“…The precise regulatory mechanism remains to be further elucidated. Perhaps, the e cacy of HS in brain edema resulting from TBI was closely associated with the downregulation of aquaporin-4 (AQP4), the restoration of brain blood barrier (BBB) integrity and the suppression of in ammatory factors including Interleukin (IL-1β), tumor necrosis factor (TNF-α), NF-κB [30].…”
Section: Discussionmentioning
confidence: 99%